The Hemostatic Effect of Bovine Peptide-B from Fibrinogen - OSBAHR, A. J (Thrombosis and Haemostasis, 1974)
Bovine peptide-B from fibrinogen was active in the hemostasis of rat tail arterioles. The time of bleeding exhibits an inverse log proportionality to the concentration of bovine peptide-B. The peptide produced a 10-fold decrease in the time of bleeding at the highest concentration tested. Prolonged incubation of the peptide with the system was unnecessary and it appeared to participate immediately as a hemostatic agent.These findings suggest that hemostasis was due to vasoconstriction since coagulation time remained constant as the bleeding time decreased with increasing concentration of peptide-B. Bovine peptide-B is interpreted as a physiological substance which probably acts on some smooth muscle receptor.